Is frozen taxidermy an alternative method for demonstration of dermatopaties? - Beste Demirci; Murat Erdem Gültiken; Mehmet Önder Karayiğit; Kerem Atalar (Eurasian Journal of Veterinary Sciences)
Taxidermy is one of the preservation techniques for mummification for centuries. In the present case, frozen taxidermy was performed on the calf with ichthyosis foetalis that is not a common disease in our country. The aim of the present study was to demonstrate this simple and inexpensive technique is able to use to preserve dermatopathic bodies. The calf with ichthyosis foetalis was prepared for dehydration and saved in the cold weather at -5 0C store for six months. After the taxidermy was thawed at room temperature, it was investigated for histo-pathologically and microbiologically. Finally, the disappeared hyperaemic areas were stained to imitate post-mortem appearance. The results revealed that hyperaemic areas were disappeared after frozen taxidermy and the skin was become though like a bark and its appearance was natural. The microbiological results showed that there was no pathogenic bacterial growth except for a few saprophyte bacilli. It is concluded that didactical embalming could be performed to demonstrate dermatophaties with the technique that does not require any chemical application.